Legal publishing in antebellum America / M.H. Hoeflich. - Hoeflich, Michael H. (Cambridge University Press, 2010)
Legal Publishing in Antebellum America presents a history of the law book publishing and distribution industry in the United States. Part business history, part legal history, part history of information diffusion, M. H. Hoeflich shows how various developments in printing and bookbinding, the introduction of railroads, and the expansion of mail service contributed to the growth of the industry from an essentially local industry to a national industry. Furthermore, the book ties the spread of a particular approach to law, that is, the 'scientific approach', championed by Northeastern American jurists to the growth of law publishing and law book selling and shows that the two were critically intertwined.